Rural labour in India : problems and policy perspective - Pandey, S.M. (ed.) (New Delhi, 1976)
The progress made by Indian economy, in the economic and social field, has been remarkable. However, it is widely agreed by observers as well as by government spokesmen that even after a quarter century of planned development our achievements, both in industry and in agriculture, are overshadowed by the continued existence of the conditions of extreme poverty among the masses in general and rural masses in particular. India's rural poor are the people who earn all or at least a significant part of their income by working as agricultural labourers. Among them may be included the landless labourers, marginal farmers, and rural artisans. A significant proportion of them belong to the scheduled and backward castes who bear the additional burden of a stigma. On the whole, these categories of the rural population have remained poor and backward essentially because of lack of literacy and organizing capacity, want of social awareness among them, and reluctance on the part of policy-makers and administrators to bring about immediate and substantial changes in our strategy for rural development, in the agrarian structure, as well as in the attitudes in life and work of teaming millions, besides other reasons. In other words, our policy for the economic development pursued in the past placed greater emphasis on mobilizing financial resources, training the manpower in skills not directly helping the rural poor, and building the essential infra-structure for the economy. It may not be incorrect to state that this emphasis obviously undermined the development of the working and living conditions of the rural poor on the one hand and more purposive and productive employment opportunities for rapidly increasing rural manpower on the other. These, no doubt, are very gigantic tasks.
Keywords: Labour and labouring classes India